Evaluation of Malnutrition Status and Related Risk Factors in Geriatric Outpatient Clinic - Tanrıöver, Özlem; Yavuzer, Hakan; Erdinçler, Deniz Suna; BALTACI, PELİN CİN (Korean Nutrition Society, 2021)
Background/objectives: Malnutrition risk and malnutrition among the elderly is a public health concern. In combating this health-related problem, it is critically important to evaluate the risk factors in a multidimensional way and to apply appropriate nutrition intervention based on the results. Subjects/methods: A cross-sectional study was conducted on 215 elderly patients (32.6% male, 67.4% female) in a geriatric outpatient clinic of a hospital in Turkey. Nutritional questionnaires that incorporated the 24-h recall method were applied to determine general characteristics of patients, their health status, nutritional habits, and daily energy and nutrient intakes. Mini Nutritional Assessment was used to determine nutritional status. Relevant anthropometric measurements were obtained. Results: The subjects' mean age was 76.1 ± 7.0 years, and the prevalence of malnutrition (n = 7) and risk of malnutrition (n = 53) among the 215 subjects was 3.2% and 24.7%, respectively. Patients with malnutrition or risk of malnutrition were found to be single, have a depression diagnosis, in an older age group, have less appetite, more tooth loss, have more frequent swallowing/chewing difficulty, and have more frequent meal skipping. In addition, mean daily energy, carbohydrate, fat, fiber, vitamin E, vitamin B1, vitamin B2, vitamin B6, vitamin C, folates, potassium, magnesium, phosphorus, iron intake, and water consumption were found to be statistically significantly low in subjects with malnutrition or risk of malnutrition. After performing regression analysis to determine confounding factors, malnutrition risk was significantly associated with marital status, loss of teeth, appetite status, and depression. Conclusions: Routine nutritional screening and assessment of the elderly should be performed. If nutritional deficiencies cannot be diagnosed early and treated, self-sufficiency in the elderly may deteriorate, resulting in increased institutionalization.
Keywords: Aged; Geriatrics; Malnutrition; Nutritional Status